Acute effects of breaking up sitting time with isometric exercise on cognition in healthy adults - Silva, Gustavo Oliveira da (2024)
The aim of this study was to analyze the acute effects of different sitting break strategies on cognition in healthy adults. Twelve physically inactive adults (8 women, 28 ± 9 years; 25.10 ± 4.90 kg/m²) randomly completed three 3 hour conditions: 2-min isometric leg extension exercise sitting breaks at 30% of maximal voluntary contraction every 30-min; 2-min light-intensity walking sitting breaks every 30-min; sitting without breaks. Stroop and Eriksen Flanker tests were used to measure cognition before and after conditions. Generalized estimated equations were used to analyze cognition responses. Data are presented as mean ± standard deviation. Stroop congruent phase decreased for all conditions (Isometric: 1.56 ± 0.20s Pre vs 1.49 ± 0.12s Post; Walking: 1.67 ± 0.22s Pre vs 1.54 ± 0.19s Post; Control: 1.69 ± 0.24s Pre vs 1.59 ± 0.26s Post; p = 0.044). There were no significant effects on Stroop incongruent phase, Stroop effect, or Eriksen-Flanker (p > 0.05 for all). In conclusion, walking or isometric exercise sitting breaks do not acutely improve cognition in healthy adults.